Association of COL2A1rs2276454, rs1793953, COL9A1rs1135056, COL11A1rs1676486 structure-forming collagens of the nucleus pulposus with degeneration of intervertebral discs L5-L4, L5-S1 - Ye. H. Pedachenko; I. H. Vasylieva; M. V. Khyzhniak; O. S. Halanta; N. H. Chopyk; O. I. Tsiubko; A. B. Hriazov; O. S. Nekhlopochyn; T. A. Ksenzov; A. B. Dmytrenko; T. A. Makarova (Zaporozhye State Medical University, 2023)
Aim. The purpose of the work was to determine the relationship between degenerative changes of the L5-S1 and L4-L5 intervertebral discs with collagen mononucleotide variants COL2A1rs2276454, rs1793953, COL9A1rs1135056, COL11A1rs1676486 among ethnic Ukrainians. Materials and methods. The following subjects were investigated: 90 persons of the case group with degeneration of the intervertebral disc L5-S1; 50 persons of the case group with degeneration of the intervertebral disc L4-L5; 66 people of the control group. The object of the study was the venous blood of patients with degenerative lesions of the intervertebral discs and healthy donors. Venous blood was obtained as a result of venipuncture. Typing of COL2A1rs2276454, COL2A1rs1793953, COL9A1rs1135056, COL11A1rs1676486 was performed using the Tag Man Universal PCR Master Mix kit (Applied Biosystems, USA) and Tag Man SNP Genotyping Assays for the determination of polymorphisms (Applied Biosystems, USA). The research was carried out by specialists in the field of molecular biology and biochemistry of the Department of Neurobiochemistry of the SI "Romodanov Neurosurgery Institute, National Academy of Medical Sciences of Ukraine", using the CFX96 device (Bio-Rrad, USA). Certificate of determination of measuring capabilities No. PT-322/21 from 07/28/2021 to 08/27/2023. Results. COL2A1rs2276454 may have a protective value for the development of degeneration of the intervertebral disc L5-S1 among men (OR (95 % CI): 0.27 (0.10-0.80), χ2 = 6.02, P = 0.015). Genotype C/T (COL9A1rs1135056) is 3.25 times more common among male patients with degeneration of the intervertebral disc L5-S1 in comparison with the female case group (OR (95 % CI): 3.25 (1.20-8.84), χ2 = 5.50, P = 0.02). The presence of the genotype G/A (COL11A1rs1676486) in the general group of patients with degeneration of the intervertebral disc L5-S1 is observed 5.46 times more often among male patients (OR (95 % CI): 5.46 (1.60-18.47), χ2 = 8.29, P = 0.004); G/A is registered 4.17 times more often among men compared to the group of women (OR (95 % CI): 4.17 (1.070-16.82), χ2 = 4.17, P = 0.04). Comparison of the odds of observing the genotype G/G, G/A, AA in the group of men with degeneration of the intervertebral disc L5-S1 showed a statistically significant 4.06 times predominance of the genotype G/A (OR (95 % CI): 4.06 (1.23-13.38), χ2 = 4.17, P = 0.04). The most probable model of heredity for COL11A1rs1676486 is dominant OR (95 % CI): 2.08 (1.03-4.21), χ2 = 4.26, P = 0.04. Associations of COL2A1rs2276454, rs1793953, COL9A1rs1135056, COL11A1rs1676486 structure-forming collagens of the gelatinous nucleus with degeneration of L5-L4 intervertebral discs were not detected. Conclusions. The COL2A1rs2276454 may be protective for the development of L5-S1 intervertebral disc degeneration in men (OR (95 % CI): 0.27 (0.10-0.80), χ2 = 6.02, Р = 0.015). COL2A1rs1793953 is not associated with degeneration of intervertebral discs L4-L5, L5-S1. С/T COL9A3rs1135056 genotype is associated with L5-S1 intervertebral disc degeneration among males (OR (95 % CI): 3.25 (1.20-8.84), χ2 = 5.50, Р = 0.02) compared with L5-S1 females. G/A COL11A1rs1676486 genotype is associated with L5-S1 intervertebral disc degeneration among male patients (OR (95 % CI): 5.46 (1.60-18.47), χ2 = 8.29, Р = 0.004) and compared to female patients (OR (95 % CI): 4.17 (1.07-16.82), χ2 = 4.17, Р = 0.04). The type of inheritance COL11A1rs1676486 is dominant.